2011
DOI: 10.2478/v10026-011-0052-3
|View full text |Cite
|
Sign up to set email alerts
|

Influence of reduction time of copper based catalysts: Cu/Al2O3 and CuCr2O4 on hydrogenolysis of glycerol

Abstract: High activity of copper based catalysts for C-O bond hydro-dehydrogenation and their poor activity for C-C bond cleavage1 have prompted an attempt to apply such catalysts in the hydrogenolysis of glycerol to 1,2-and 1,3-propanediol. In the present study the infl uence of hydrogen reduction time of the Cu/ Al 2 O 3 and CuCr 2 O 4 copper catalysts on glycerol conversion and selectivity of transformation to propanediols and by-products was studied. At fi rst a general comparison was made between the commercial ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
(13 reference statements)
1
1
0
Order By: Relevance
“…It is known that CuAl 2 O 4 spinel structure is the major active phase for HDO reactions. Based on the EDX analysis for CuAlO phase, the molar ratio of Cu, Al, and O is roughly 0.6/1.1/2.5 (or 1.8/3.3/7.5 for another spot on the same sample), which is consistent with the composition of spinel CuAl 2 O 4 species or its dimer (dicopper aluminum oxide, Cu 2 Al 4 O 7 ) structure. The EDX analysis of another phase CaCuAlO phase is consistent with a structure such as Ca 5 Cu 3 Al 6 O 17 .…”
Section: Results and Discussionsupporting
confidence: 58%
“…It is known that CuAl 2 O 4 spinel structure is the major active phase for HDO reactions. Based on the EDX analysis for CuAlO phase, the molar ratio of Cu, Al, and O is roughly 0.6/1.1/2.5 (or 1.8/3.3/7.5 for another spot on the same sample), which is consistent with the composition of spinel CuAl 2 O 4 species or its dimer (dicopper aluminum oxide, Cu 2 Al 4 O 7 ) structure. The EDX analysis of another phase CaCuAlO phase is consistent with a structure such as Ca 5 Cu 3 Al 6 O 17 .…”
Section: Results and Discussionsupporting
confidence: 58%
“…The initial glycerol conversion and 1,2-PDO selectivity were found to be stable over 250 h. 74 In another instance, the influence of reduction time on the activity of Cu/ Al 2 O 3 and CuCr 2 O 4 catalysts revealed that the Cu/Al 2 O 3 catalyst prepared by precipitation and reduced for 8 h showed the highest glycerol conversion of 59% with 77.4% and 1.9% selectivities to 1,2-PDO and 1,3-PDO, respectively, at 200 °C, 30 bar H 2 for 24 h. The catalysts reduced for 8 h, contains both Cu 0 and Cu 1+ particles, however, the extended reduction time of 24 h caused the sintering of copper particles, which was responsible for lowering of glycerol hydrogenolysis activity. 75 Akiyama and co-workers used commercial copper catalysts supported on Al 2 O 3 , Cr 2 O 3 , ZnO, and SiO 2 as well as Ni on SiO 2 for gas-phase hydrogenolysis of glycerol at an ambient pressure of H 2 in which complete glycerol conversion and high selectivity (96.9%) to 1,2-PDO was achieved by maintaining temperature gradients (200-120 °C). 76,77 The pre-reduction step of Cu catalyst could be avoided by co-impregnation with silver however, the activity of CuAg/Al 2 O 3 was lower than the parent pre-reduced Cu/Al 2 O 3 .…”
Section: Supported Cu Based Catalystsmentioning
confidence: 99%